A Type I Interferon and IL-10 Induced by Orientia tsutsugamushi Infection Suppresses Antigen-Specific T Cells and Their Memory Responses - Min, Chan-Ki; Kim, Hong-II; Ha, Na-Young; Kim, Yuri; Kwon, Eun-Kyung; Yen, Nguyen Thi Hai; Youn, Je-In; Jeon, Yoon Kyung; Inn, Kyung-Soo; Choi, Myung-Sik; Cho, Nam-Hyuk (Frontiers in Immunology, 2018)
Despite the various roles of type I interferon (type I IFN) responses during bacterial infection, its specific effects in vivo have been poorly characterized in scrub typhus caused by Orientia tsutsugamushi infection. Here, we show that type I IFNs are primarily induced via intracellular nucleic acids sensors, including RIG-I/MAVS and cGAS/STING pathways, during O. tsutsugamushi invasion. However, type I IFN signaling did not significantly affect pathogenesis, mortality, or bacterial burden during primary infection in vivo, when assessed in a mice model lacking a receptor for type I IFNs (IFNAR KO). Rather, it significantly impaired the induction of antigen-specific T cells and reduced memory T cell responses. IFNAR KO mice that recovered from primary infection showed stronger antigen-specific T cell responses, especially Th1, and more efficiently controlled bacteremia during secondary infection than wild type mice. Enhanced IL-10 expression by macrophages in the presence of type I IFN signaling might play a significant role in the suppression of antigen-specific T cell responses as neutralization or knock-out of IL-10 increased T cell responses in vitro. Therefore, induction of the type I IFN/IL-10 axis by O. tsutsugamushi infection might play a significant role in the suppression of T cell responses and contribute to the short longevity of cell-mediated immunity, often observed in scrub typhus patients.